2006
DOI: 10.1002/chin.200644185
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of Exemestane — Synthesis and Evaluation of Aromatase Inhibition.

Abstract: Steroids U 0300Derivatives of Exemestane -Synthesis and Evaluation of Aromatase Inhibition.-Several derivatives of the irreversible aromatase inhibitor exemestane (IV) are synthesized, which show reduced inhibitory potency towards aromatase compared to the parent compound (IV). -(GOERLITZER*, K.; BONNEKESSEL, C.; JONES, P. G.; PALUSCZAK, A.; HARTMANN, R. W.; Pharmazie 61 (2006) 7, 575-581; Inst. Pharm. Chem., TU Braunschweig, D-38106 Braunschweig, Germany; Ger., Abstr. Eng.) -M. Kowall 44-185

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Although the stereochemistry at the 6-position was not assigned in the current paper, we speculate the stereo orientation for the 6 substitute is “ α ” for both synthesized 6-EXE-cys and 6-17 β -DHE-cys based on the proton coupling constant between the proton at the 4-position and the proton at the 6-position of both EXE-cys and 17 β -DHE-cys conjugates. For 6-substituted steroids, long-distance coupling between H-4 and H-6 in 1 H NMR will be observed only when the 6-substituent is in the α position ( Chin and Warren, 1972 ; Schneider et al, 1973 ; Numazawa and Oshibe, 1994 ; Numazawa and Yamaguchi, 1998 ; Görlitzer et al, 2006 ). In an analysis of a series of 6-substituted phenylaliphatic steroids, Numazawa and Yamaguchi (1998) demonstrated that proton coupling between the hydrogens at the 4- and 6-positions was only observed for the 6 α -substituted, but not the 6 β -substituted, phenylaliphatic steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Although the stereochemistry at the 6-position was not assigned in the current paper, we speculate the stereo orientation for the 6 substitute is “ α ” for both synthesized 6-EXE-cys and 6-17 β -DHE-cys based on the proton coupling constant between the proton at the 4-position and the proton at the 6-position of both EXE-cys and 17 β -DHE-cys conjugates. For 6-substituted steroids, long-distance coupling between H-4 and H-6 in 1 H NMR will be observed only when the 6-substituent is in the α position ( Chin and Warren, 1972 ; Schneider et al, 1973 ; Numazawa and Oshibe, 1994 ; Numazawa and Yamaguchi, 1998 ; Görlitzer et al, 2006 ). In an analysis of a series of 6-substituted phenylaliphatic steroids, Numazawa and Yamaguchi (1998) demonstrated that proton coupling between the hydrogens at the 4- and 6-positions was only observed for the 6 α -substituted, but not the 6 β -substituted, phenylaliphatic steroids.…”
Section: Discussionmentioning
confidence: 99%
“…SCXRD analysis revealed that EX crystallizes in the orthorhombic space group P2 1 2 1 2 1 (Gö rlitzer et al, 2006), whereas the co-crystal crystallizes in the monoclinic space group P2 1 ; hence EX and TH are independent asymmetric moieties in the unit cell with Z = 2, as depicted in Table 1. Structural analysis revealed that EX and its co-crystal are both composed of four transfused rings (A-D).…”
Section: Resultsmentioning
confidence: 99%
“…Compound (I) shares structural and physicochemical similarities with the natural substrate of the enzyme, androstenedione (Busetta et al, 1972), and with exemestane (Gorlitzer et al, 2006), an important aromatase inhibitor, suggesting a common aromatase recognition mechanism. In particular, the three compounds have very hydrophobic scaffolds and two hydrogen-bond acceptors at equivalent positions, viz.…”
Section: Commentmentioning
confidence: 96%
“…The cyclopentane B-nor ring assumes a 9-envelope conformation [puckering parameters: q 2 = 0.435 (2) Å and ' 2 = 288.2 (3) ; pseudorotation and asymmetry parameters: Á = 181.3 (2), ' m = 44.2 (1), ÁC s (9) = 1.0 (2), ÁC 2 (8,9) = 22.4 (2) ]. The pseudo-torsion angle C19-C10Á Á ÁC13-C18 of 6.9 (2) indicates that the B-nor steroid molecule is twisted compared with androstenedione or exemestane, for which values of À1.57 and 0.1 (2) , respectively, were determined by Busetta et al (1972) and Gorlitzer et al (2006). This twist can be understood as a normal consequence of the replacement of the six-membered B ring by a five-membered ring.…”
Section: Figurementioning
confidence: 99%